Legal Protection for Parking Service Users to Standard Agreements Containing Exclusion Clauses - Utama, Eka Satya Kartika; Tjoanda, Merry; Kuahaty, Sarah Selfina (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The high mobility of society can be seen from the increasing number of vehicles. These vehicles certainly need a place to park, because it is impossible to use them continuously without being parked. However, in the managementof parking lots, parking managers still include exoneration clauses, both on parking tickets and at parking locations.Purposes of the Research: Review and analyze the legal protection of parking service users who apply an exoneration clause.Methods of the Research: This research is a normative legal research, using a statue approach and conceptual approach. The sources of legal materials used a primary, secondary, and tertiary legal material, then analyzed qualitatively.Results Main Findings of the Research: The form of legal protection for users of parking services containing an exoneration clause is to give protection to the fulfillmaent of consumer rights as users of parking services, where the parking management is obliged to ensure the safety of vehicles parked in parking facilities and is responsible for providing compensation in case of damaged or loss. If the parking management continues to violate the law, sanctions will be imposed, both administrative and criminal sanctions.